CREATIVITY - A PREREQUISITE FOR THE FORMATION OF PROFESSIONAL COMPETENCES IN SPECIALISTS OF TECHNICAL DIRECTION OF TRAINING - Bakharev, N.P (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The solution of the problem of training a modern world-class technician is considered depending on the multilevel needs of the economy, society today and tomorrow. Specialists of technical direction - graduates of Russian universities should have competence in the field of design, development, operation, machines, devices, equipment of various purpose, which should correspond to the level of the best world models, and, in the end, exceed them in various characteristics and indicators. Technical tasks, which have to be solved today by a specialist, bachelor and master of modern production (machine-building, electrical engineering, electric power), regardless of the direction of activity, are proposed to be suspended, divided into three levels. The first creative level is the perfect mastery of skills to support and ensure the operability of known domestic and foreign technical solutions with not significant modernization and adjustment of the design of the device or technological system in case of such necessity and need. The second creative level is a significant modernization and qualitative improvement of various technical and economic parameters, output characteristics of known technical solutions (devices, methods) without changing the basic idea of functioning and architecture of the system of building and implementing its consumer purpose. The third creative level is solving problems or technical problems using theory and methodology of creativity, invention. The technical tasks of the third level involve the elimination of significant contradictions and the creation of a fundamentally new design or technology with qualitative and quantitative characteristics that significantly exceed the existing solutions. Problems tasks,solved with the help of creativity theory are available to students of the direction of training master (engineer), trained in technical universities on adjusted educational programs with introduction of a block of disciplines of creativity theory and invention. Solutions to technical problems of the third level allow to apply in the educational process a qualitatively new approach, from the point of view of methodology, in the formation of professional competences - is the creation of inventions of devices, methods and useful models in the existing education system built according to federal state educational standards. The transition to the creative level (third) of master 's training will require an adjustment of the educational program on the basis of the introduction of a system of comprehensive measures that ensure the formation of creativity among students in solving various types of problem technical problems. The main thing in the adjustment is to change the working programs of all special disciplines of the curriculum on the basis of introducing elements of creativity into practical and project tasks.